INTEGRASI TEORI KONSTRUKTIVISME DALAM PLATFORM PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE (AI) DI PASRAMAN NONFORMAL: PELUANG DAN TANTANGAN PENGIMPLEMENTASIANYA - Dewi, Ni Luh Made Larasanthi Komala; Swana, I Putu (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2026)
This study examines how the integration of constructivism theory into an Artificial Intelligence (AI)-based learning platform at Pasraman Nonformal presents a new paradigm in the world of digital education. This study uses a literature review method, which involves searching various scientific references related to the issues under review. The findings of this study are that constructivism theory emphasizes the active role of students (brahmacari) in constructing knowledge through experience, reflection, and social interaction. AI-based learning platforms have great potential to support constructivism principles through personalized learning, adaptive feedback, and the provision of a learning environment that is responsive to individual needs. The AI platforms that can be used to support learning activities in pasraman are Kahoot, Canva, and ChatGPT. However, the implementation of this integration also faces various challenges, such as limitations in technological infrastructure, the digital literacy gap between educators (Acarya) and students (brahmacari), as well as issues of ethics and data privacy. The success of this integration greatly depends on appropriate pedagogical design, human resource readiness, and educational policies that support the sustainable use of technology